1988
DOI: 10.1029/jb093ib10p11583
|View full text |Cite
|
Sign up to set email alerts
|

Dipole/quadrupole family modeling of paleosecular variation

Abstract: Contrary to previous claims that the VGP scatter and its latitude variation deduced from the present field are atypical of those for the past 5 m.y., it is shown that it is in fact typical when correctly calculated. A simple and effective model for the paleosecular variation of lavas is developed by using this important observation together with the dipole and quadrupole families from dynamo theory. The model predicts a latitudinal variation of VGP scatter, S, given by S=A2λ2+B2 , where λ is the latitude and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
188
3
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(222 citation statements)
references
References 21 publications
28
188
3
3
Order By: Relevance
“…All new VGPs obtained on this study yield lesser colatitudes (maximum value is 28.3º) than generally adopted 45º cut-off angle (Johnson et al, 2008). We obtained S F =16.0 with S U =25.5 and S L =8.1 (upper and lower limits respectively) which reasonably agree to the model G of McFadden et al (1988McFadden et al ( , 1991 fit to the McElhinny and McFadden (1997) and Johnson et al (2008) databases for the last 5 Myr (Fig. 8b and 9).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…All new VGPs obtained on this study yield lesser colatitudes (maximum value is 28.3º) than generally adopted 45º cut-off angle (Johnson et al, 2008). We obtained S F =16.0 with S U =25.5 and S L =8.1 (upper and lower limits respectively) which reasonably agree to the model G of McFadden et al (1988McFadden et al ( , 1991 fit to the McElhinny and McFadden (1997) and Johnson et al (2008) databases for the last 5 Myr (Fig. 8b and 9).…”
Section: Resultssupporting
confidence: 73%
“…A simple method to estimate the PSV consists in observing of the angular standard deviation (ASD) of virtual geomagnetic poles (VGPs) for a given locality. Several combinations of dipole and non-dipole components predict the ASD characteristic of PSV with latitude (McFadden et al, 1988(McFadden et al, , 1991Lawrence et al, 2006;Johnson et al 2008)). Johnson et al (2008) reported a detailed synthesis of a new generation of paleomagnetic data compilations.…”
Section: Introductionmentioning
confidence: 99%
“…Our model for the Gaussian coefficients is also different in concept from that proposed by MCFADDEN et al (1988), who introduced the dipole and quadrupole families of spherical harmonic coefficients. The dipole family includes all coefficients in which the degree and order differ by odd numbers, while their quadrupole family includes those whose degree and order differ by an even number.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, McFadden et al (1988) proposed Model G in which harmonics belonging to the dipole family (i.e., ge or h7 with £ + m = odd) and quadrupole family (t + m = even) are decoupled in the generation of the 616 M. KoNo geodynamo, and, as a consequence, the angular variance of the VGPs can be written as the sum S2 = A2A2 + B2,…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the form of Eq. (2) was deduced from the analysis of a field model for 1965 (McFadden et al, 1988), but recently it was pointed out (Hulot and Gallet, 1996) that this cannot match even the field of recent past (e.g. 1800), and so justification for using Eq.…”
Section: Introductionmentioning
confidence: 99%